The HIV/AIDS epidemic among young people in China between 2005 and 2012: results of a spatial temporal analysis. Issue 3 (24th August 2016) - Zhang, X; Tang, W; Li, Y; Mahapatra, T; Feng, Y; Li, M; Chen, F; Li, P; Xing, J; Qian, S; Ge, L; Bu, K; et al.
Abstract : Objectives: Despite a recent increase in the HIV/AIDS epidemic among young people in China, youth‐specific HIV data are limited. Methods: In total, 56 621 individuals with HIV/AIDS, aged 15–24 years, registered in the Case Reporting System of China between 2005 and 2012 and having complete spatial information were included in the present analysis. Spatial autocorrelation (general and local) and space−time scanning were performed using theArc GIS 10.2 andSa TScan 9.3 software, respectively. Results: During 2005−2012, the number of reported HIV/AIDS cases and the proportion of HIV cases increased while the proportion of AIDS cases decreased. Sexual contact became the predominant route of transmission in later years. Spatial analysis showed marked geographical variations in HIV infection among young people throughout China during 2005−2012. The number of new hotspots increased over time. They were mainly localized to southeastern coastal areas, southwestern frontier provinces or autonomous regions (of Guangxi, Yunnan and Sichuan) and Beijing municipality. Later these hotspots disappeared and new hotspots were found in the northeast of the country. Significant clusters of HIV‐positive cases were identified in three different time periods, which indicated high HIV transmission among young Chinese people in the recent past. The risk of HIV infection was highest in the first cluster (2009–2012; this cluster was the largest in size) covering the provinces of Guizhou and Yunnan, the Chongqing municipality, Guangxi, and the province of Sichuan. The second cluster (2010–2012) was mostly located in Shanghai, South Jiangsu, Zhejiang and South Anhui, while the third cluster (2010–2012) was located in Beijing and Tianjin. Conclusions: Target‐specific comprehensive behavioural interventions are urgently needed to contain the HIV epidemic among young people.